My lots are in Thy Hands: Sortilege and its practitioners in Late Antiquity - Luijendijk, AnneMarie; Klingshirn, William E.; Jenott, Lance (Religions in the Graeco-Roman world, 2019)
Front Matter -- Copyright page -- -- Preface -- Figures -- Abbreviations -- Notes on Contributors -- Introduction -- The Literature of Lot Divination /AnneMarie Luijendijk and William E. Klingshirn -- The Instruments of Lot Divination /William E. Klingshirn -- Fateful Spasms: Palmomancy and Late Antique Lot Divination /Salvatore Costanza -- Hermēneiai in Manuscripts of John’s Gospel: an Aid to Bibliomancy /Kevin Wilkinson -- Hermeneutics and Divination: a Unique Syriac Biblical Manuscript as an Oracle of Interpretation /Jeff W. Childers -- Secondhand Homer /Michael Meerson -- Sortes Biblicae Judaicae /Pieter W. van der Horst -- The Sortes Barberinianae within the Tradition of Oracular Texts /Randall Stewart -- Oxyrhynchus and Oracles in Late Antiquity /Alexander Kocar -- Sortes, Scribality, and Syncretism: Ritual Experts and the Great Tradition in Byzantine Egypt /David Frankfurter -- Sortilege between Divine Ordeals and “Secular” Justice: Aspects of Jurisdiction in (Ritual) Texts from Ptolemaic and Roman Egypt /Franziska Naether -- Freakonomika: Oracle as Economic Indicator in Roman Egypt /David M. Ratzan -- “I Do Not Wish to Be Rich”: the ‘Barbarian’ Christian Tatian Responds to Sortes /Laura Salah Nasrallah -- “Only Do Not Be of Two Minds”: Doubt in Christian Lot Divination /AnneMarie Luijendijk -- Back Matter -- Bibliography.